Estimation of Private Consumption Function of Iran: Autoregressive Distributed Lag Approach to Co-integration - Nikbin, Behnam; Panahi, Saman (International Journal of Economics and Financial Issues, 2016)
Considering consumption due to its pivotal role in economic growth and also aggregate demand and specially its long-run analysis have always been in the center of attention. In this study, we have estimated private consumption function, using ARDL approach and employing annual data during 1978-2012. Short-run elasticity of private consumption function regarding to its lag is 0.50 and to GDP is approximately 0.56. Also, the latter amount for long-run elasticity is 1.13. Furthermore, the estimation demonstrates a negative correlation between inflation and private consumption in both long-run and short-run relationships. ECM is estimated as well, and the coefficient is equal to -0.49 which shows the pace in which the private consumption function adjusts to its long-run equilibrium. Keywords: Consumption function, ARDL approach, ECM JEL Classifications: C13 C22 E21